Pola Pembelajaran Pendidikan Agama Islam Pada Masa Pandemi Covid-19 - Nurul Iflaha; Elok Rufaiqoh (Prodi Pendidikan Agama Islam IAI Al-Qodiri Jember, 2021)
The learning pattern is the form used by educators in delivering learning materials and dynamizing the teaching and learning process. Before the outbreak that hit the world, namely the Covid-19, learning patterns in educational institutions were direct, namely the learning and teaching process took place in the classroom where students developed knowledge, thinking skills and psychomotor skills through direct interaction with learning resources designed in the syllabus. and lesson plans in the form of learning activities. However, during the pandemic, the world of education is required to apply indirect learning patterns to prevent crowds that make it easier to contract the disease. There are several patterns that are applied in the learning process, including online, offline, blended methods, home visits and others. The application of some of these patterns in Islamic Religious Education learning is adjusted to the design that has been prepared by the teacher by maximizing the transfer of knowledge and inculcating educational values.